Lithiation–Substitution of N-Boc-2-phenylazepane - Aeyad, Tahani; Williams, Jason D.; Meijer, Anthony J. H. M.; Coldham, Iain (Synlett, 2017)
Preparation of 2,2-disubstituted azepanes was accomplished from N-tert-butoxy(N-Boc)-2-phenylazepane by treatment with butyllithium then electrophilic quench. The lithiation was followed by in situ ReactIR spectroscopy and the rate of rotation of the carbamate was determined by variable temperature (VT)-NMR spectroscopy and by DFT studies. Most electrophiles add α to the nitrogen atom but cyanoformates and chloroformates gave ortho-substituted products. Cyclic carbamates were formed from an aldehyde or ketone electrophile. Kinetic resolution with sparteine was only poorly selective. Removal of the Boc group promoted cyclization to a homoindolizidine or an isoindolinone.
Keywords: alkylation; heterocycles; lithiation; lithium